Kontekst geopolityczny kryzysu na Ukrainie (2013–2014) i zaangażowanie władz polskich w jego rozwiązanie - Olszyk, Sabina (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2016)
W artykule przedstawiono specyfikę zaangażowania podmiotów międzynarodowych w konflikt na Ukrainie na przełomie 20132014 r. Atrakcyjność tego państwa wynikała w zasadniczej mierze z jego położenia geopolitycznego oraz pozycji jako kraju buforowego między Wschodem a Zachodem. Omówiono ponadto działania władz polskich podejmowane w kierunku zażegnania sporu, wynikające z rosnącego poczucia zagrożenia ze strony Federacji Rosyjskiej.

The paper presents the specifics of the involvement of international actors in the conflict of Ukraine at the turn of 2013–2014. The country was considered attractive primarily due to its geopolitical position and the country being a buffer between the East and the West. The steps taken by the Polish authorities in the settlement of a dispute arising from the growing sense of threat from the Russian Federation are also discussed.
Geopolitical context of the crisis in Ukraine (2013–2014) and the Polish authorities’ commitment to solve it
Keywords: kryzys na Ukrainie 2013–2014; EuroMajdan; geopolityka; crisis in Ukraine (2013–2014); Euromaidan; geopolitics